Mesoproterozoic and Paleoproterozoic subcontinental lithospheric mantle domains beneath southern Patagonia: Isotopic evidence for its connection to Africa and Antarctica - Mundl, Andrea; Ntaflos, Theodoros; Ackerman, Lukas; Bizimis, Michael; Bjerg, Ernesto Alfredo; Hauzenberger, Christoph A. (Geology)
New isotopic studies on mantle xenoliths from Santa Cruz Province, southern Patagonia, Argentina, reveal that at least three discrete subcontinental lithospheric mantle (SCLM) domains—the Deseado Massif, Tres Lagos, and Pali Aike—form the southernmost part of South America. Re-Os systematics yield early Paleoproterozoic (up to 2.5 Ga) SCLM formation ages (rhenium depletion ages, TRD) for Pali Aike spinel peridotites, while samples from the Deseado Massif and Tres Lagos indicate a younger SCLM origin with Neoproterozoic to Mesoproterozoic (0.9–1.3 Ga) and Mesoproterozoic to late Paleoproterozoic (1.3–1.9 Ga) TRD ages, respectively. Hf-Sr-Nd isotopic compositions indicate metasomatic overprinting of the majority of the samples, which, however, has not affected the Os isotopic system. Based on similar formation ages, the geological evolution of the Deseado Massif is most likely connected to the evolution of the Namaqua-Natal belt of South Africa. TRD ages from SCLM domains underneath Tres Lagos and Pali Aike indicate a common origin with crustal sections from Shackleton Range, Antarctica, positioning the southern tip of South America closer to west Antarctica in the reconstructed Rodinia supercontinent than previously assumed. Fil: Mundl, Andrea. University of Vienna.Department of Lithospheric Research; Austria Fil: Ntaflos, Theodoros. University of Vienna. Department of Lithospheric Research; Austria Fil: Ackerman, Lukas. Academy of Sciences of the Czech Republic; República Checa. Czech Geological Survey; República Checa Fil: Bizimis, Michael. University of South Carolina; Estados Unidos Fil: Bjerg, Ernesto Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Bahía Blanca. Instituto Geológico del Sur; Argentina. Universidad Nacional del Sur; Argentina Fil: Hauzenberger, Christoph A. University of Graz. Institute for Earth Sciences; Austria